2008
DOI: 10.1007/s11999-008-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Patient Dose and Associated Radiogenic Risks from Limb Lengthening

Abstract: Limb-lengthening procedures include a series of radiographic examinations to follow the lengthening process and callus formation. We quantified ionizing radiation exposure during lengthening treatment and estimated the risks associated with this exposure in 53 patients undergoing lengthening procedures. Field size and tube voltage of all radiographs and fluoroscopy time during surgery were recorded. According to conversion factor tables of organ doses, the cumulative organ dose was estimated. Location of lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It is obvious from Table 2 that the average number of X-ray views required is 15. The number of X-rays for following similar cases treated with bone transport by other workers is 30 X-ray views per patient 24. This indicates that nearly 2 times less X-rays are required for the fractures monitored by electrical conduction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is obvious from Table 2 that the average number of X-ray views required is 15. The number of X-rays for following similar cases treated with bone transport by other workers is 30 X-ray views per patient 24. This indicates that nearly 2 times less X-rays are required for the fractures monitored by electrical conduction.…”
Section: Discussionmentioning
confidence: 94%
“…The number of X-rays for following similar cases treated with bone transport by other workers is 30 X-ray views per patient. 24 This indicates that nearly 2 times less X-rays are required for the fractures monitored by electrical conduction. The minimum effective dose to produce each view of leg X-ray is 1.54 μSv.…”
Section: Discussionmentioning
confidence: 99%
“…Schiedel et al ., 18 showed that femur lengthening may result in a higher cumulative organ dose which meant higher radiogenic risks to patients compared with tibial lengthening. Moreover, tibial lengthening has no interference on the structure of the hip joints and can preserve the ROM of hip without any obstacle to a future THA procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Such frequent exposure to X-rays can cause marrow depression and malignancy [ 1 – 3 ]. Sometimes even around 30 X-rays are needed in a single patient till union [ 4 ]. X-ray analysis is not always consistent, as maturity in viewing a fracture radiograph depends on individual medical practitioner's skill and experience which leads to interobserver and intraobserver variations.…”
Section: Introductionmentioning
confidence: 99%